Cooling of rotating electrical machines : fundamentals, modelling, testing and design - Staton, David (Software engineer); Chong, Eddie; Pickering, Stephen; Boglietti, Aldo (IET energy engineering series, 2022)
Thermal management is an issue with all electrical machines, including electric vehicle drives and wind turbine generators. Excessively high temperatures lead to loss of performance, degradation and deformation of components, and ultimately loss of the system. Cooling of Rotating Electrical Machines: Fundamentals, modelling, testing and design provides a foundation of heat transfer and ventilation for the design of machines. It offers a range of practical approaches to the thermal design, as well as design data and case studies. Chapters cover fundamentals of heat transfer, fluid flow, thermal modelling of electrical machines, computational methods for modelling ventilation and heat transfer such as finite element methods and computational fluid dynamics, thermal test methods, and application of design methods. Intended for engineers and researchers working in either academia or machine design companies, this book provides sound insights into the phenomena of heat transfer and fluid flow, giving readers an understanding of how to approach the thermal design of any machine.